GPS plus GLONASS CORS Processing: The Asian-Pacific APREF Case - Nardo, A.; Huisman, L.; Teunissen, Peter (SPRINGER-VERLAG BERLIN, 2011)
The ongoing completion of the GLONASS system asks for a new assessment of its performance in relation to CORS network processing. The recent established Asian-Pacific Reference Frame (APREF) offered such an opportunity. Daily double-difference network solutions have been computed both for GPS-only and GPS + GLONASS processings. The formal precision of the daily solutions as well as the time series of the coordinates and reference frame parameters, derived from multi-annual combinations (2. 5 years) of the daily solutions, have been used to assess the effect of the additional GLONASS observations on the estimates of the coordinates and the stability of the reference frame. Results show that, for 24-h data batches, GLONASS adds little improvement when compared to GPS-only processing.